2018
DOI: 10.1111/nan.12473
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone D accelerates disease progression in the SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: The results suggest that EpoD accelerates disease progression in the SOD1 mouse model of ALS, and highlights that the pathophysiological involvement of microtubules in ALS is an evolving and underappreciated phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
0
20
1
Order By: Relevance
“…Although we did not see a significant loss of axons, dendrites or spines by 7 days post-injury in the current study, there was certainly observable axonal damage throughout the ipsilateral cortex and white matter. Interestingly, the epothilone D treatment regime used in the current study did not have a protective effect on degenerating axons and our previous study using a mouse model of amyotrophic lateral sclerosis showed chronic epothilone D exposure may be detrimental to axons ( Clark et al, 2018 ). However, using an in vitro model of structural axonal injury we have previously shown that low dose epothilone D has a protective effect on injured axons by increasing injury-induced axonal sprouting ( Brizuela et al, 2015 ), indicating that microtubule stabilization within damaged axons may be partially responsible for the previously described neuroprotective effect of epothilone D and may have feed forward effects with regard to dendritic spine innervation.…”
Section: Discussioncontrasting
confidence: 55%
“…Although we did not see a significant loss of axons, dendrites or spines by 7 days post-injury in the current study, there was certainly observable axonal damage throughout the ipsilateral cortex and white matter. Interestingly, the epothilone D treatment regime used in the current study did not have a protective effect on degenerating axons and our previous study using a mouse model of amyotrophic lateral sclerosis showed chronic epothilone D exposure may be detrimental to axons ( Clark et al, 2018 ). However, using an in vitro model of structural axonal injury we have previously shown that low dose epothilone D has a protective effect on injured axons by increasing injury-induced axonal sprouting ( Brizuela et al, 2015 ), indicating that microtubule stabilization within damaged axons may be partially responsible for the previously described neuroprotective effect of epothilone D and may have feed forward effects with regard to dendritic spine innervation.…”
Section: Discussioncontrasting
confidence: 55%
“…Together these studies provided impetus to harness microtubule-stabilizing drugs such as epothilone B for therapy. More recently, epothilone D was shown to facilitate recovery of hind limb function after spinal cord injury in rats (Sandner et al, 2018 ), yet in the SOD1 G93A mouse model of ALS, epothilone D accelerated disease progression (Clark et al, 2018 ), indicating that more work is needed in a variety of models.…”
Section: Epothilones In Animal Models Of Neurodegeneration and Spinalmentioning
confidence: 99%
“…epothilone D alters microtubule associated proteins involved in microtubule regulation and stability. Our laboratory 26,43 , and others 44 , have previously used acetylated tubulin levels to measure the stabilising potential of Epothilone D. We have previously reported that cortical neurons treated for two hours with 100 nM of EpoD have markedly increased levels of tubulin acetylation in vitro. Indeed, in the current study we treated 10DIV culture cortical neurons with EpoD and evaluated a number of microtubule stability markers and microtubule associated proteins (MAPs).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has previously shown that 0.1 nM concentrations of EpoD promote axonal regeneration in a scratch assay injury model, supporting the use of sub nanomolar concentrations of EpoD to improve neuronal growth 26 . More recently we have shown a mixture of beneficial and detrimental outcomes follow therapeutic administration of EpoD in an ALS mouse model 43 . Wild type littermates in this study receiving the same dose of EpoD (2 mg/kg) showed no aberrant behavioural, neuronal degeneration or glial activation phenotypes.…”
Section: Discussionmentioning
confidence: 99%